2020
DOI: 10.1089/vbz.2019.2458
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic Diseases in Oman: Successes, Challenges, and Future Directions

Abstract: Objective: This article describes the situation analysis of endemic and emerging zoonoses, and includes prevention and control of zoonoses in Oman. It also suggests possible recommendations toward elimination and risk reduction of emerging zoonoses. Methods: Epidemiologic information has been drawn from official to assess the situation. There has been significant progress in reducing the risk of brucellosis, Middle East Respiratory Syndrome Coronavirus, Crimean-Congo hemorrhagic fever, and cutaneous leishmania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Furthermore, strong intersectoral collaboration and coordination between the animal and human health sectors at regional, national and international levels is an utmost necessasity to prevent, control and eliminate emerging zoonoses. Urgent and strategic adoption of One health approach along with an integrated surveillance, monitoring and networking system, appropriately supported by rapid and confirmatory laboratory investigation facilities, effective immunization/vaccination and therapeutic approaches along with adopting appropriate prevention and control measures are altogether highly anticipated to curb the emerging zoonoses globally (Dhama et al, 2013;Awaidy et al, 2020). Besides these, due attention towards public awareness and collaborative disease control strategies need to be implemented in the right directons amomg different sectors and stake-holders (medical, veterinary, government departments, non-government organizations, NGOs) and various regulatory health agencies for implementing warranted interventions for effectively checking the transmisión and spread, and control of the emerging, re-emerging and zoonotic threats posed by infectious pathogens.…”
Section: Revisiting the One Health Approach In The Context Of Covid-1mentioning
confidence: 99%
“…Furthermore, strong intersectoral collaboration and coordination between the animal and human health sectors at regional, national and international levels is an utmost necessasity to prevent, control and eliminate emerging zoonoses. Urgent and strategic adoption of One health approach along with an integrated surveillance, monitoring and networking system, appropriately supported by rapid and confirmatory laboratory investigation facilities, effective immunization/vaccination and therapeutic approaches along with adopting appropriate prevention and control measures are altogether highly anticipated to curb the emerging zoonoses globally (Dhama et al, 2013;Awaidy et al, 2020). Besides these, due attention towards public awareness and collaborative disease control strategies need to be implemented in the right directons amomg different sectors and stake-holders (medical, veterinary, government departments, non-government organizations, NGOs) and various regulatory health agencies for implementing warranted interventions for effectively checking the transmisión and spread, and control of the emerging, re-emerging and zoonotic threats posed by infectious pathogens.…”
Section: Revisiting the One Health Approach In The Context Of Covid-1mentioning
confidence: 99%
“…The mortality rate of patients was 35%. 1,7,13 The exact mechanism underlying the seasonal pattern of viral infection between April and June is also not well understood. It has been hypothesized that it may be due to the camel birthing season, when there is intermingling of mature and young camels.…”
Section: Epidemiologymentioning
confidence: 99%
“…3 Symptoms may range from mild to severe and include fever, cough, diarrhea, and shortness of breath. 1,4 The disease presentation is typically more severe in patients with comorbid health problems. Approximately one-third of diagnosed patients do not survive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the slaughterhouse infrastructure and their practices are unsatisfactory, and dogs (owned and stray) have access to infected organs [13,15]. A study conducted in the Middle Atlas showed a high prevalence of CE infestation in dogs, ranging from 23.5% to 38.8% in owned dogs and from 51.3% to 68.5% in stray dogs [16].…”
Section: Introductionmentioning
confidence: 99%